New christians, converted hindus, jesuits, and the inquisition - Franco, José Eduardo (2021)
This paper analyses the complex relationship between Jesuits, New Christians, converted Hindus, and the Inquisition. The collaboration of Jesuits with the Holy Office did not prevent voices from being raised within the Society of Jesus against the tribunal’s practices, which were observed with caution by the first Jesuit leaders. For their part, conversos were initially welcomed into the Society and even assumed high positions in the Society, such as the second superior general. Despite the difficult history of intolerance and inquisitorial persecution against New Christians, in the seventeenth century, Jesuits in Portugal became prominent advocates of their cause. In turn, Hindu conversion strategies fueled disputes and tensions between the Society of Jesus and the Inquisition of Goa. Their strained relations make these disputes an important historiographical subject for understanding many of the plots and dramas of Portuguese society under the Old Regime.